2016
DOI: 10.1123/jab.2015-0185
|View full text |Cite
|
Sign up to set email alerts
|

Normalization to Maximal Voluntary Contraction is Influenced by Subacromial Pain

Abstract: In this study, we aimed to determine if electromyography (EMG) normalization to maximal voluntary isometric contractions (MVIC) was influenced by subacromial pain in patients with subacromial impingement syndrome. Patients performed MVICs in unique testing positions for each shoulder muscle tested before and after subacromial injection of local anesthetic. In addition to collection of MVIC data, EMG data during an arm elevation task were recorded before and after injection. From a visual analog pain scale, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Although the MVC method is commonly used for healthy subjects, the RVC method is good for patients who find it difficult to exert maximal or submaximal power because of severe joint pain. 8,20 Given the characteristics of our patients with CTA or OA with large cuff tears, it was impossible to perform MVC. Therefore, standing erect with both arms at the sides was adopted as the reference posture.…”
Section: Discussionmentioning
confidence: 99%
“…Although the MVC method is commonly used for healthy subjects, the RVC method is good for patients who find it difficult to exert maximal or submaximal power because of severe joint pain. 8,20 Given the characteristics of our patients with CTA or OA with large cuff tears, it was impossible to perform MVC. Therefore, standing erect with both arms at the sides was adopted as the reference posture.…”
Section: Discussionmentioning
confidence: 99%
“… 53 The use of maximal contractions can be a source of discomfort and also can lead to an overestimation of muscle activation. 54 The type of resistance applied during MVCs can also be a source of variability. In this study, the resistance was manually applied since this method is the most reported in the literature 38 but the use of straps is also commonly reported.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings should be interpreted in the light of the study limitations. First, since maximal muscle activation can cause discomfort and overestimation of muscle strength (21), caution is recommended when normalizing to an MVIC in patients with shoulder pain. To avoid overestimation of the percentage of muscle activation, MVIC tests should happen in a pain-free or reduced-pain condition (21).…”
Section: Discussionmentioning
confidence: 99%
“…After clinical examination, EMG electrodes were placed. To allow for relevant EMG comparisons between subjects and studies, it is recommended to normalize EMG activity to a maximum voluntary isometric contraction (MVIC) (21). Most hEDS/HSD patients were unable to perform the previously described MVICs (22), since many of these positions are challenging for unstable shoulders and provoke pain symptoms and apprehension.…”
Section: Methodsmentioning
confidence: 99%